2013
DOI: 10.1364/josaa.30.000342
|View full text |Cite
|
Sign up to set email alerts
|

Transparency perception: the key to understanding simultaneous color contrast

Abstract: The well-known simultaneous color contrast effect is traditionally explained in terms of visual color constancy mechanisms correcting for the confounding influence of ambient illumination on the retinal color signal. Recent research, however, suggests that the traditional gross quantitative laws of simultaneous color contrast, which are readily compatible with this functional explanation, should be revised and replaced by others, which are not readily understandable in terms of this perspective. Here, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 53 publications
5
27
1
Order By: Relevance
“…It is therefore reasonable that X-junctions are used as a cue for perceptual transparency. This is supported by the finding illustrated in Figure 1c that transparency is usually not perceived without X-junctions (but see Kersten, 1991;Ekroll & Faul, 2013). However, X-junctions alone are not sufficient to elicit an impression of transparency ( Figure 1b).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…It is therefore reasonable that X-junctions are used as a cue for perceptual transparency. This is supported by the finding illustrated in Figure 1c that transparency is usually not perceived without X-junctions (but see Kersten, 1991;Ekroll & Faul, 2013). However, X-junctions alone are not sufficient to elicit an impression of transparency ( Figure 1b).…”
Section: Introductionsupporting
confidence: 61%
“…However, the specific nature of the suggested nonlinear adaptation process and the question how adaptation can be taken into account in the filter model remains unclear. Together, these findings suggest that perceptual transparency is not only closely related to simultaneous contrast (Ekroll & Faul, 2013) but also influenced by successive contrast. The results in the opaque case suggest that a higher perceived plausibility of an illumination change has a positive influence on the degree of constancy.…”
Section: Discussionmentioning
confidence: 66%
“…The crucial factor is that the main currency of both models is contrast. The importance of contrast for the perception of lightness has been repeatedly pointed out in the recent past (Ekroll & Faul, 2013;Schmid & Anderson, 2014). However, the present results also raise questions about how the visual system might extract and represent information about contrast statistics that might either have to be pooled over a relatively large area in an image or, if not present in single images, would require some representation of those statistics over time.…”
Section: Discussionsupporting
confidence: 54%
“…The idea that the visual system might treat photometric variations as spatial variations in the illumination has been suggested before (Allred et al, 2012), and Ekroll and Faul (2013) have demonstrated empirically that certain combinations of luminances at low contrast evoke percepts of transparency that were not intended in the stimulus design. So it is possible that, unbeknownst to the experimenter, in the present stimulus the respective local darkening or lightening of the target surround has acted as a cue to image segmentation.…”
Section: Model Modificationsmentioning
confidence: 99%
“…This suggests that any gain control processes that arise along the two axes are not entirely independent or that the gamut expansion effect cannot be solely due to gain control processes. Second, the fact that the gamut expansion effect is larger when the targets and surrounds are along the same color axis suggests that the gamut expansion effect cannot be solely a consequence of scission or transparency mechanisms (Ekroll & Faul, 2013;Ekroll et al, 2004). Once the texture of the surround becomes clearly visible, it should not be possible to decompose the target into a transparent overlay and an underlying surface because the target and the surround do not share the same textural properties.…”
Section: Gamut Expansion Ratio ¼ Distance From Test Target To Match Tmentioning
confidence: 99%